Preparation and Evaluation of Long-Acting Injectable Levocetirizine Prodrug Formulation - Jun-hyun Ahn (Pharmaceutics, 2025)
Background/Objectives: Levocetirizine (LCZ) is a second-generation antihistamine with minimal central nervous system effects. However, its short half-life necessitates daily dosing, potentially reducing adherence in pediatric populations. This study aimed to develop a long-acting injectable LCZ formulation by synthesizing lipophilic prodrugs and evaluating their physicochemical stability, enzymatic hydrolysis, and pharmacokinetics in vivo. Methods: Two prodrugs of LCZ, LCZ decanoate (LCZ-D) and LCZ laurate (LCZ-L), were synthesized via esterification with alkyl alcohols. The compounds were characterized using NMR, FT-IR, and DSC. Prodrugs were formulated with an oil-based vehicle (castor oil and benzyl benozate), and their hydrolysis was evaluated using porcine liver esterase (PLE) and rat plasma. Pharmacokinetic profiles were assessed in Sprague Dawley rats after oral or intramuscular administration. Stability was tested at 25 °C, 40 °C, and 60 °C for 6 weeks. Results: LCZ-D and LCZ-L exhibited first-order hydrolysis kinetics, with rates following the order of PLE (2.0 > 0.5 units/mL) > plasma > PLE (0.2 units/mL). The Cmax of LCZ-D and LCZ-L were 13.95 and 5.12 ng/mL, respectively, with corresponding AUC0–45d values of 6423.12 and 2109.22 h·ng/mL. Formulations containing excipients with lower log P values led to increased systemic exposure. All formulations maintained therapeutic plasma concentrations for over 30 days. The inclusion of the antioxidant BHT (0.03% v/v) improved oxidative stability, reducing degradation at 60 °C from 4.72% to 1.17%. Conclusions: All formulations demonstrated potential for the long-acting delivery of LCZ, maintaining therapeutic plasma levels for over 30 days. Moreover, the release behavior and systemic exposure could be effectively modulated by excipient selection.